Lapidarium : the secret lives of stones - Judah, Hettie (Penguin Books, an imprint of Penguin Random House LLC, 2023)
"Inspired by the lapidaries of the ancient world, this book is a collection of true stories about sixty different stones that have influenced our shared history. Through the realms of art, myth, geology, philosophy, and power, the author tells the story of humanity through the minerals and materials that have allowed humans to evolve and create. Lapidarium uses the stories of these sixty stones to explore how human culture has formed stone, and the roles stone has played in forming human culture"--